Case Report: Salvation of a congested SCIP flap with a modified “chemical leech” technique - Zhao, Yong; Yang, Xianquan; Zhu, Shaobo; Yu, Aixi (Frontiers in Surgery, 2024)
The superficial circumflex iliac artery perforator (SCIP) flap is a widely accepted workhorse flap for covering defects. Although the success rate of SCIP flaps is currently high, flap failure occurs occasionally due to venous congestion. Venous re-anastomosis is the ideal rescue method but is sometimes limited by poor venule condition. The “chemical leech” technique could relieve venous congestion without venous re-anastomosis. However, owing to insufficient offloading, this technique is less effective in free flaps than in fasciocutaneous flaps, especially large-volume flaps. In this case report, we modified the “chemical leech” technique by adding a venous catheter. Congested blood was drained in a 2-way manner, both through a venous catheter and the skin incisions. On the first day, congested blood was mainly drained through the catheter. Intermittent heparin irrigation was required to maintain the blood flow. On days 2 and 3, as the microcirculation improved, the flow regulator was turned down to reduce blood loss. Blood loss through the catheter decreased dramatically from day 4 onward. This was probably due to thrombosis in and around the catheter. Another pathway through the skin still worked until the establishment of microcirculation, which occurred on day 8. Compared to previous “chemical leech” therapy, the modified “chemical leech” therapy was more reliable and could help drain the congested blood on venule level in addition to capillary level, making the blood drainage more efficient.